EVALUACIÓN DEL TIEMPO Y TEMPERATURA DE INCUBACIÓN EN EL PROCESO DETOXIFICACIÓN DE UNA TOXINA TETÁNICA - Duarte, Marcela; Laboratorio Producción de Tétanos. Instituto Nacional de Salud. Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
In order to reduce the incubation time and temperature in the Tetanic Toxin detoxification process, different times and temperature were evaluated; taking crops in process that were grown in tetanus Lab production of the National Institute of Health. To determine the exact da y of detoxification a logis tic model was established. The toxin was incubate at 4,22 and 37°C to estimate the optim temperature. Then the physical-chemical characteristics like (pH), and the biologycal characteristics (Lf/mL, unspecific, specific toxicity and antigenicy) of the toxoid were verified. The best conditions for the process are: 25 days of incubation at 37°C. With the characteristics above, yearly there is a possibility to get a profit of 1.513.350 doses that represen! $37.833.750 for the production of the Tetanic Toxin